Application of Islamization of Human Knowledge and relevantization of Islamic sciences - Mughal, Muhammad Junaid; Mumtaz Ali, Mohammad; Chisti, Siddiq Ali (Department of Islamic Studies, Riphah International University, Islamabad, 2025)
The concept of the Islamization of Human Knowledge (IOHK) stands as one of the most promising yet contentious intellectual initiatives of Islamic revival, drawing considerable attention from both Muslim and non-Muslim thinkers in the modern era. The founders of IOHK have worked diligently to frame it as an epistemological and methodological response to the challenges facing the Muslim Ummah. Despite the sincere dedication and tireless efforts of scholars, this groundbreaking project has been marred by various misconceptions. Skepticism has led to fundamental misunderstandings regarding its scope, objectives, and methodology. Thus, this study explores the potential application of the term "relevantization" to Islamic sciences, referred to as Islamic Revealed Knowledge Disciplines (IRKDs) at International Islamic University Malaysia (IIUM). The study observes that, despite numerous challenges and criticisms, the IOHK project has made gradual progress in refining its framework, scope, objectives, and methodology since its inception. Its scope has broadened from producing textbooks and Islamizing disciplines to advancing Islamic thought and methodology. Although IOHK has contributed substantially to intellectual discourse and clarified its concepts, practical implementation remains a challenge. Achieving its goals demands more focused and collaborative efforts on a holistic level. The study underscores the obstacles that scholars must address to move the project forward